Search for keV-scale sterile neutrinos with the first KATRIN data - Aker, Max; Rodejohann, Werner (The European physical journal. C, Particles and fields, 2023)
In this work we present a keV-scale sterile-neutrino search with a low-tritium-activity data set of the KATRIN experiment, acquired in a commissioning run in 2018. KATRIN performs a spectroscopic measurement of the tritium β-decay spectrum with the main goal of directly determining the effective electron anti-neutrino mass. During this commissioning phase a lower tritium activity facilitated the measurement of a wider part of the tritium spectrum and thus the search for sterile neutrinos with a mass of up to 1.6 ke V. We do not find a signal and set an exclusion limit on the sterile-to-active mixing amplitude of sin2 0 < 5 x 10 -4 (95% C.L.) at a mass of 0.3 keV. This result improves current laboratory-based bounds in the sterile-neutrino mass range between 0.1 and 1.0 keV.
Online veröffentlicht: 29. August 2023
Gesehen am 29.01.2024